Sons of Anarchy Season 6 Disc 5 - Sagal, Katey; Coates, Kim, 1958-; Flanagan, Tommy, 1965-; FX Productions; Fox 21 (Firm); Twentieth Century Fox Home Entertainment, Inc. (Beverly Hills, CA 20th Century Fox Home Entertainment, 2014)
Ride with the Sons of Anarchy, and relive the adrenaline-chared show's most controversial and tension filled season ever.
Title from container.
Originally broadcast as episodes of season 6 of the television series in 2013.
Special features: Audio commentary on "A mothers work" featuring Kurt Sutter, Paris Barclay Maggie Siff and Katey Sagal; gag reel; Anarchy afterword season finale; The reaper calls; Sons for Sandy.
Katey Sagal, Kim Coates, Tommy Flanagan, Charlie Hunnam, Maggie Siff, Mark Boone Jr.
DVD, region 1, NTSC, widescreen (1.78:1); Dolby Digital 5.1.
English dialogue; French or Spanish subtitles; subtitled for the deaf and hard of hearing; closed-captioned.
Keywords: Illegal arms transfers -- Drama; Motorcycle clubs -- Drama; Drama; Television crime shows; Video recordings for the hearing impaired